KECERDASAN SPIRITUAL MEMODERASI GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI PADA KINERJA PENYUSUN LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (LAKIP) - Hama Ratu, Noldy Imanuel; Ratna Sari, Maria Mediatrix; Dwija Putri, I G. A. M. Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018, 2018)
The adoption of public accountability is a way to account for success or failure in order to achieve the organization's mission is the background of this research. The purpose of this study to determine the influence of leadership style and organizational culture on the performance of the compilers LAKIP moderated by spiritual intelligence. The sample used in this research is nonprobability sampling with census technique. Respondents of this study amounted to 80 people. Primary data used in this study is poured through a statement in the form of questionnaires. Hypothesis test used moderation regression analysis. Hypothesis testing results prove the performance of LAKIP compilers influenced by leadership style and organizational culture. The influence of organizational culture on the performance of government accountability performance reporting reporter can be moderated by spiritual intelligence, while the influence of leadership style on performance of accountability report reporter of government agency performance can not be moderated by spiritual intelligence.